2004
DOI: 10.1002/14651858.cd004391.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular arteether for treating severe malaria

Abstract: More trials with a larger number of participants are needed before a firm conclusion about the efficacy and safety of arteether can be reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In the first study, no statistically significant difference was found in the number of deaths or other outcomes, such as coma recovery time, parasite clearance time and fever clearance time. 13 However, in the second study the combined adverse outcome of either death or neurological sequelae was significantly less common in the artemether group. 12 After the meta-analysis mentioned above, new clinical trials in which artemether has been compared with quinine for the treatment of cerebral malaria in children have been carried out.…”
Section: Hmwe Hmwe Kyu a And Eduardo Fernández Amentioning
confidence: 86%
“…In the first study, no statistically significant difference was found in the number of deaths or other outcomes, such as coma recovery time, parasite clearance time and fever clearance time. 13 However, in the second study the combined adverse outcome of either death or neurological sequelae was significantly less common in the artemether group. 12 After the meta-analysis mentioned above, new clinical trials in which artemether has been compared with quinine for the treatment of cerebral malaria in children have been carried out.…”
Section: Hmwe Hmwe Kyu a And Eduardo Fernández Amentioning
confidence: 86%
“…There is substantially less published information on artemotil than for artemether. Absorption is slower and more erratic, with some patients having undetectable plasma artemotil until more than 24 h after administration (Afolabi & Okoromah ; Li et al . ; Pareek et al .…”
Section: Pharmacology Of Antimalarial Drugsmentioning
confidence: 99%
“…It may also be more effective than other artemisinin derivatives because of its oil solubility, longer half life, and increased chemical stability. 4 AE contains a stable endoperoxide bridge, this bridge is proposed to be responsible for its antimalarial activity. AE also possesses gametocytocidal properties through inhibiting parasite transmission.…”
Section: Introductionmentioning
confidence: 99%